Can payments for environmental services reduce deforestation and forest degradation? - Wunder, Sven (Center for International Forestry Research, 2009)
Payments for environmental services (PES) have the potential to become effective, cost-efficient and equitable instruments for implementing REDD+ on the ground. PES require certain preconditions to be satisfied, in particular land stewardship with ‘the right to exclude third parties’, which is not granted in many forest frontiers. Using spatial targeting toward high-threat, high-service and low-cost areas can dramatically improve PES carbon results. Failing to use these design features can make PES inefficient.